A Natural Hydrogel with Prohealing Properties Enhances Tendon Regeneration. Issue 36 (18th March 2022) - Dang, Ruyi; Chen, Liling; Sefat, Farshid; Li, Xian; Liu, Shilin; Yuan, Xulei; Ning, Xiaoqiao; Zhang, Yu Shrike; Ji, Ping; Zhang, Ximu
Abstract: Tendon regeneration and reduction of peritendinous adhesion remain major clinical challenges. This study addresses these challenges by adopting a unique hydrogel derived from the skin secretion of Andrias davidianus (SSAD) and taking advantage of its biological effects, adhesiveness, and controllable microstructures. The SSAD‐derived hydrogel contains many cytokines, which could promote tendon healing. In vitro, leach liquid of SSAD powder could promote tendon stem/progenitor cells migration. In vivo, the SSAD‐derived hydrogel featuring double layers possesses strong adhesiveness and could reconnect ruptured Achilles tendons of Sprague‐Dawley rats without suturing. The intimal SSAD‐derived hydrogel, with a pore size of 241.7 ± 21.0 µm, forms the first layer of the hydrogel to promote tendon healing, and the outer layer SSAD‐derived hydrogel, with a pore size of 3.3 ± 1.4 µm, reducing peritendinous adhesion by serving as a dense barrier. Additionally, the SSAD‐derived hydrogel exhibits antioxidant and antibacterial characteristics, which further contribute to the reduction of peritendinous adhesion. In vivo studies suggest that the SSAD‐derived hydrogel reduces peritendinous adhesion, increases collagen fiber deposition, promotes cell proliferation, and improves the biomechanical properties of the regenerated tendons, indicating better functional restoration. The SSAD‐derived bilayer hydrogel may be a feasible biomaterial for tendon repair in the future. Abstract : A dual‐layered skin secretion of Andrias davidianus (SSAD)‐derived hydrogel to promote tendon regeneration and antiadhesion is reported. The strong adhesiveness allows the SSAD hydrogel to reconnect ruptured tendons. The inner hydrogel with a large pore size allows cells growth and the outer layer of the hydrogel with a small pore size could serve as a barrier to prevent peritendinous adhesion.